The Ecological Model of Prisons in Iran with Emphasis on Prisoners’ Behavioral Reform (Case Study: Tehran Prisons Organization) - Mohammadzadeh, Pedram; Hosseini gol afshani, Seyed Ahmad; Sajadi Jagharq, Seyed Abdullah; Zamani Moghaddam, Afsaneh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aimed to design and analyze a comprehensive ecological model of prisons in Iran with a focus on behavioral reform of inmates, using Tehran Prisons Organization as the case study. Methods and Materials: This research employed an exploratory mixed-methods design with a qualitative emphasis. The qualitative phase was conducted using a phenomenological approach through in-depth, semi-structured interviews with 16 experts, including senior prison managers and academic faculty with lived experience in the prison system. Data collection continued until theoretical saturation was reached. Thematic analysis was used for qualitative data analysis, based on six systematic stages involving open coding, axial coding, and theme development using ATLAS.ti version 9 software. The conceptual framework was refined based on insights from the interviews, literature review, and expert validation, resulting in a three-level thematic model. Findings: hematic analysis of expert interviews led to the identification of five overarching dimensions and multiple sub-themes influencing inmate behavior reform: prison environment (including physical conditions, social atmosphere, and security), reformative and educational programs (including vocational and academic training, psychological counseling), social and familial support (including reintegration support and family contact), economic and occupational conditions (including employment opportunities and financial aid), and judicial and managerial systems (including legal procedures and decision-making processes). These themes were integrated into a conceptual ecological model that captures the multi-dimensional and systemic factors contributing to rehabilitation and behavioral transformation in prison settings. Conclusion: The ecological model developed in this study provides a practical and theoretical foundation for understanding and improving inmate behavior reform through systemic and multidimensional strategies. It emphasizes the need for integrated interventions across environmental, educational, psychological, social, and legal domains to foster sustainable reintegration outcomes.